PROBLEMATIKA FAKTOR STUNTING PADA WILAYAH PESISIR (Studi Kebijakan Pada Kabupaten Buton Tengah Tahun 2022) - Azhari; Dedihasriadi; Muis (Journal Publicuho, 2024)
The aim of this research is to determine Problematic Stunting Factors In Coastal Areas through a Policy Study in Central Buton Regency in 2022. This research is qualitative research with a case study approach. Data collection was carried out using interview methods, various document studies and observations. The results of this research show that the lack of coordination between various institutions in the regional TPPS Team, such as BKKBN, Village Government, and Community Health Centers, caused high stunting rates in Central Buton Regency, Southeast Sulawesi in in 2022. Apart from that, the existence of societal myths, inadequate parenting patterns, early marriage and poor sanitation also play a role in increasing stunting rates in the area. Financial constraints also caused many work programs within the TPPS Team to not be realized.